A metaphor called "Mozart" - Kirkeby, Ole Fogh (HERMES - Journal of Language and Communication in Business, 2000)
In the following essay I shall venture on the ocean of metaphor, reducing the rashness of this project by the use of the well-worn boat of philosophy. I shall ask four questions: 1. Is it possible to realise metaphor through thought, action or emotion? 2. What is the opposite of metaphor? 3. Does an alternative to metaphorical thinking exist? 4. Does an alternative metaphorical thinking exist? However, should my project fail, perhaps the raft of metaphor itself might carry me safe to the island ruled by Ariel and Prospero, and where other shipwrecked once were met with soft music.